Sex and propinquity as variables affecting the attitudes of Miagao, residents toward UPV females. - Canieso, Romina Lou G.
This study was undertaken to determine whether physical proximity or propinquity and sex are significant variables affecting the attitudes of Miagao residents toward UPV females. The sample, composed of 138 males and females residing in one rural barangay and one poblacion barangay in Miagao, was chosen through the stratified random sampling with proportional allocation. The attitude measurement scaling procedure ensured the reliability of the Likert-type attitude scale which was pretested on thirty (30) male and female accidental sample residents of Barangay Sapa, Miagao. The two-way analysis of variance (ANOVA) at .05 level of significance showed that sex, propinquity, and their interaction did not significantly affect the attitudes of Miagao, residents toward UPV females.